How do I work this?
x-y=3 x+2y=-3
Answers
Answered by
11
`
`
x - y = 3 ......(1)
x + 2y = -3 .......(2)
Now, solve both (1) and (2) by elimination method,
And multiply (1) by 2
2x - 2y = 6
1x + 2y = -3
__________
3x = 3
__________
x = + 1
Put value of x in (1)
+ 1 - y = 3
- y = + 3 - 1
- y = 2
y = - 2
`
x - y = 3
x = 3 + y ......(1)
x + 2y = - 3 .....(2)
Put value of x in (2)
3 + y + 2y = - 3
3 + 3y = - 3
3y = - 6
y = - 2
Put value of y in (1)
x = 3 - 2
x = + 1
marjhingoree:
Using the substitution method
Answered by
8
Hi friend...
________
Here's your answer....
_________________
x-y = 3 -------(1)
x+2y = -3 ----(2)
by substracting (1) from (2) we get
x+2y=-3
x-y=3
- + -
________
3y= -6
or, y = -2
now, by putting y= -2 in (1) we get
x-(-2) = 3
or, x+2 = 3
or, x = 1
so, x= 1 and y= -2
_______________________________________
Hope it helps you.... please mark as brainliest ☺☺☺❤❤❤
________
Here's your answer....
_________________
x-y = 3 -------(1)
x+2y = -3 ----(2)
by substracting (1) from (2) we get
x+2y=-3
x-y=3
- + -
________
3y= -6
or, y = -2
now, by putting y= -2 in (1) we get
x-(-2) = 3
or, x+2 = 3
or, x = 1
so, x= 1 and y= -2
_______________________________________
Hope it helps you.... please mark as brainliest ☺☺☺❤❤❤
Similar questions
Physics,
8 months ago
Physics,
8 months ago
Social Sciences,
8 months ago
Math,
1 year ago
Sociology,
1 year ago